Near-infrared indocyanine green videoangiography (ICGVA) and intraoperative computed tomography (iCT): Are they complementary or competitive imaging techniques in aneurysm surgery? - Schnell, Oliver; Morhard, Dominik; Holtmannspötter, Markus; Reiser, Maximilian; Tonn, Jörg Christian; Schichor, Christian (Acta Neurochirurgica, 2012)
Background: In this pilot study we compared advantages and drawbacks of near-infrared indocyanine green videoangiography (ICGVA) and intraoperative computed tomography (iCT) to investigate if these are complementary or competitive methods to acquire immediate information about blood vessels and potential critical impairment of brain perfusion during vascular neurosurgery. Methods: A small subset of patients (n=10) were prospectively enrolled in this feasibility study and received ICGVA immediately after placement of the aneurysm clips. An intraoperative cranial CT angiography (iCTA) was followed by dynamic perfusion CT scan (iCTP) using a 40-slice, sliding-gantry, CT scanner. The vascular patency of major (aneurysm bearing) arteries, visualisation of arising perforating arteries and brain perfusion after clip application were analysed with both techniques. Results: The ICGVA was able to visualise blood flow and vascular patency of all major vessels and perforating arteries within the visual field of the microscope, but failed to display vessels located within deeper areas of the surgical field. Even small coverage with brain parenchyma impaired detection of vessels. With iCTA high image quality could be obtained in 7/10 cases of clipped aneurysms. Intraoperative CTA was not sufficiently evaluable in one PICA aneurysm and one case of a previously coiled recurrent aneurysm, due to extensive coil artefacts. Small, perforating arteries could not be detected with iCTA. Intraoperative CTP allowed the assessment of global blood flow and brain perfusion in sufficient quality in 5/10 cases, and enabled adequate intraoperative decision making. Conclusion: A combination of ICGVA and iCT is feasible, with very good diagnostic imaging quality associated with short acquisition time and little interference with the surgical workflow. Both techniques are complementary rather than competing analysing tools and help to assess information about local (ICGVA/iCTA) as well as regional (iCTA/iCTP) blood flow and cerebral perfusion immediately after clipping of intracranial aneurysms. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Aneurysm clipping; ICGVA; iCTA; Vascular neurosurgery